Estimation of the dependence parameters of nuclear structural materials hardness on the content of gas impurities: an interval approach - Potanina, Т.V.; Yefimov, O.V.; Pylypenko, M.M. (Вопросы атомной науки и техники, 2021)
The applications of the interval and standard probabilistic approaches for verifying the reliability of the results of an experiment studying the mechanical properties of nuclear materials are compared. The presence of “outliers” in a sample of hardness values for hafnium ingots is studied with for fixed oxygen mass content. The situation of measurement error limitation without reliable information about its distribution is considered. The correctness of the application of numerical methods of interval analysis for processing experimental data under conditions of uncertainty and noisy experimental data is shown. Determination of the dependence of the Brinell hardness of refined hafnium samples on the mass oxygen content was performed by a combination of methods: removal of anomalous measurements by interval analysis methods and approximation of data from truncated samples by the method Levenberg-Marquardt minimization. Проведено порівняльний аналіз застосування інтервального і стандартного ймовірнісного підходів для перевірки достовірності результатів експерименту з вивчення механічних властивостей ядерних матеріалів. Досліджується вибірка значень твердості зразків злитків гафнію при однаковому масовому вмісті кисню на наявність викідів. Розглядається ситуація обмеженості похибки вимірювань без достовірної інформації про її розподіл. Показана коректність застосування чисельних методів інтервального аналізу для обробки експериментальних даних в умовах невизначеності і наявності «шуму» в них. Визначення залежності твердості за Брінеллем рафінованих зразків гафнію від масового вмісту кисню здійснено за допомогою комбінації методів: видалення аномальних значень методами інтервального аналізу з наступною апроксимацією даних з усічених вибірок методом мінімізації Левенберга-Марквардта. Проведен сравнительный анализ применения интервального и стандартного вероятностного подходов для проверки достоверности результатов эксперимента по изучению механических свойств ядерных материалов. Исследуется выборка значений твердости образцов слитков гафния при одинаковом массовом содержании кислорода на наличие выбросов. Рассматривается ситуация ограниченности погрешности измерений без достоверной информации о ее распределении. Показана корректность применения численных методов интервального анализа для обработки экспериментальных данных в условиях неопределенности и зашумленности. Определение зависимости твердости по Бринеллю рафинированных образцов гафния от массового содержания кислорода выполнено комбинацией методов: удаление аномальных измерений методами интервального анализа с последующей аппроксимацией данных из усеченных выборок методом минимизации Левенберга-Марквардта.